A home‐based approach to demonstrate column and thin layer chromatography during the COVID ‐19 pandemic - Ediriweera, Meran Keshawa; Fernando, Dilusha; Thoradeniya, Tharanga; Warawitagei, Dilanthi Hewa; Siridewa, Kithmini (Biochemistry and molecular biology education, 2023)
The COVID-19 pandemic caused several educational challenges. Conducting laboratory experiments was an uphill task during the pandemic. Here, we developed a low-cost and reliable home-based experimental setup to teach column and thin layer chromatography (TLC) using silica gel granules available at home. Powdered silica gel, prepared by grinding silica gel granules, was used as the stationary phase. Iso-propyl alcohol, purchased from a pharmacy, was diluted with water and used as the mobile phase. A food coloring was chromatographically separated using the designed column. Moreover, TLC plates were prepared using powdered silica gel and a drop of food coloring was separated on TLC plates using the same mobile phase. In the article, we show our experiences by providing methods used to implement this experimental setup. We assume that this experimental setup will be helpful for other universities, research institutes and schools to develop online laboratory curricula to demonstrate basic chromatography techniques required for subjects such as chemistry, biochemistry and biology.